Examined life [2008] - Taylor, Astra ([s.l.] : ICA films, 2009)
- Cornel West : examining yourself ##- Avital Ronell : paths that lead nowhere ##- Peter Singer : the shallow pond ##- Kwame Anthony Appiah : the cosmopolitan ##- Martha Nussbaum : the capabilities approach ##- Cornel West : truth as a way of life ##- Michael Hardt : becoming capable of democracy ##- Slavoj Žižek : ecology as ideology ##- Judith Butler & Sunaura Taylor : what can a body do? ##- Cornel West : rejecting romanticism.
film
Keywords: Taylor, Astra